A survey on beliefs and attitudes of trainee surgeons towards placebo. Issue 1 (December 2016) - Baldwin, Mathew; Wartolowska, Karolina; Carr, Andrew
Abstract Background The aim of this study was to investigate the beliefs and attitudes of trainee surgeons regarding placebo interventions, in surgical practice and in research, and to compare them to those of senior orthopaedic surgeons. Methods An invitation to participate in an online survey was sent to all the email addresses in the members' database of the British Orthopaedic Trainees Association (BOTA). Results All 987 members of BOTA were invited to participate in the survey and 189 responded (19 %). The majority of trainees think that the placebo effect is real (88 %), has therapeutic benefits (88 %) and that placebo manipulations are permissible (98 %). Sixty per cent of respondents agree that placebo can be used outside of research, most commonly, to distinguish between organic and non-organic symptoms (36 %). Trainees are more likely than senior surgeons to use placebo for pain management (34 % vs. 12 %). They are mainly concerned about the risk of side effects associated with the use of placebo (80 %) and prefer placebo interventions with minimal invasiveness. Seventy-three per cent respondents would recruit patients into the proposed randomised controlled surgical trial. Conclusions The views regarding efficacy, permissibility and indications for placebo among trainees are similar to those of orthopaedic consultants. Orthopaedic trainees regard placebo as permissible and show willingness to recruit into placebo-controlled trials. However, they seem to have limited understanding of mechanisms of placebo effect and underestimate its ubiquity.